2015
DOI: 10.1128/aac.00478-15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug-Drug Interactions between Daclatasvir and Methadone or Buprenorphine-Naloxone

Abstract: cHepatitis C virus (HCV) infection is common among people who inject drugs, including those managed with maintenance opioids. Pharmacokinetic interactions between opioids and emerging oral HCV antivirals merit evaluation. Daclatasvir is a potent pangenotypic inhibitor of the HCV NS5A replication complex recently approved for HCV treatment in Europe and Japan in combination with other antivirals. The effect of steady-state daclatasvir (60 mg daily) on stable plasma exposure to oral opioids was assessed in non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The DDI studies conducted during the development program of DCV demonstrate that it has few or no clinically relevant DDIs with HCV DAA regimen partners [16–20], first-line antiretrovirals [23–26], immunosuppressants [12], narcotic analgesics [28], gastric acid-reducing agents [35], or other common concomitant medications (e.g., hormonal contraceptives [32], antidepressants [SSRIs; data on file], and benzodiazepine sedatives) [13]. Furthermore, real-world data, although limited, suggest that the regimen of DCV/SOF has a favorable DDI profile, compared with other NS5A inhibitor-based regimens [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DDI studies conducted during the development program of DCV demonstrate that it has few or no clinically relevant DDIs with HCV DAA regimen partners [16–20], first-line antiretrovirals [23–26], immunosuppressants [12], narcotic analgesics [28], gastric acid-reducing agents [35], or other common concomitant medications (e.g., hormonal contraceptives [32], antidepressants [SSRIs; data on file], and benzodiazepine sedatives) [13]. Furthermore, real-world data, although limited, suggest that the regimen of DCV/SOF has a favorable DDI profile, compared with other NS5A inhibitor-based regimens [39].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of steady-state DCV on the exposure of oral opioids (methadone and buprenorphine/naloxone) administered at stable doses was assessed in non-HCV-infected, opioid-dependent adults in Study AI444-064 [28]. During co-administration, the exposures (AUCs) of DCV and R-methadone (active methadone enantiomer) were unaffected, and clinically insignificant increases in the exposures of buprenorphine (31%) and norbuprenorphine (62%) were observed; the 90% GMRs of opioid AUCs were contained entirely within the literature-derived ranges of no effect (R-methadone, 0.7–1.23; buprenorphine and norbuprenorphine, 0.5–2.0) and no dose adjustments during co-administration were required.…”
Section: Ddis and Dosing Guidance With Commonly Prescribed Concommentioning
confidence: 99%
See 1 more Smart Citation
“…DAC is a P-glycoprotein substrate and shares with MET CYP3A4 as a major metabolizing enzyme; moreover, MET is also metabolized by CYP2B6 [9]. The common metabolism by CYP3A4 could give a rationale for a possible DDI between the 2 drugs; however, in a study by Garimella et al [4], no DDI was observed. Nevertheless, this study was conducted on healthy individuals with normal liver function.…”
Section: Discussionmentioning
confidence: 70%
“…In a study by Garimella et al [4] the drug-drug interaction profile between daclatasvir (DCV; 60 mg) and MET was studied in 14 subjects without CHC, observing no significant interaction.…”
Section: Introductionmentioning
confidence: 99%